Tow-Dimensional Monic Polynomials For Solving Linear And Nonlinear Partied Differential Equations - et. al., Marina Shirwan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, two dimensional monic polynomial technique is present for solving linear and nonlinear partied differential equations. The application of the method to boundary value problems leads to algebraic systems. The procedure in handling solutions of differential equations using Monic polynomial is to express the derivatives of a function in terms of its values by operational matrices. The suggested method can be used to facilitate greatly the setting up of the algebraic systems to be obtained solving differential equations. The effective application of the method is demonstrated by three examples.